Pengaruh Humanistic Leadership, Strategic Power Leadership, Visionary Leadership dan Knowledge Management terhadap Kinerja SDM Karyawan Retail di Kabupaten Semarang - Familia Artha; Satria Avianda Nurcahyo; Teguh Harso Widagdo; Ahmad Ali (Lembaga Yasin AlSys, 2026)
In an era of increasingly intense competition in the retail industry, companies are required to enhance the quality of human resource (HR) management in order to sustain business continuity and achieve optimal performance. Although HR performance plays a crucial role in supporting operational success, employee performance achievements are still found to fall short of targets, thereby necessitating an analysis of leadership and knowledge management factors that influence performance improvement. This study aims to analyze the effects of Humanistic Leadership, Strategic Power Leadership, Visionary Leadership, and Knowledge Management on the human resource performance of retail employees in Semarang Regency. A quantitative approach was employed with purposive sampling, involving 100 retail employee respondents. Data were collected using a five-point Likert scale questionnaire and analyzed through validity and reliability tests, classical assumption tests, and multiple linear regression with the aid of SPSS version 26. The results show that Humanistic Leadership, Strategic Power Leadership, Visionary Leadership, and Knowledge Management fall within the good to very good categories and have a significant effect on HR performance, with Knowledge Management emerging as the most dominant factor in enhancing work effectiveness. These findings confirm that the application of humanistic, strategic, and visionary leadership styles, accompanied by structured and optimal knowledge management, can improve employee quality and productivity, while also providing a basis for retail management in designing more effective human resource development policies.